RESULTS OF UNRELATED ALLOGENEIC STEM CELL TRANSPLANTATION: A SINGLE CENTER EXPERIENCE - Muhammed Murati; Yakup Ünsal; Güler Delibalta; Serdar Bedii Omay (Hematology, Transfusion and Cell Therapy)
Objective: Evaluation of data from unrelated hematopoietic stem cell transplants performed in our transplant center. Methodology: At the Private Emsey Hospital Adult Stem Cell Transplantation Unit were evaluated retrospectively between 2016 and 2023 to Allogeneic hematopoietic stem cell transplantations performed on 76 patients with different diagnoses from unrelated donors. Results: Data of patients with a mean age of 41.9 years were retrospectively analyzed. All donors were from a Turkish stem cell bank and 51% had HLA 1 allele incompatibility. 28 transplants were performed between different genders. Average follow-up was 17.3 months. Neutrophil engraftment occurred in an average of 18.1 days. Acute GVHD was detected in 26% and chronic GVHD in 41%. 1-year overall survival was 37% and disease-free survival was 32%. Conclusion: Non-relative stem cell transplantation is an important option especially in hematological diseases where there is no family donor and allogeneic transplantation is required. It has been observed that non-relative data performed in our clinic are similar to data from other centers.